The Meaning of Life According to Transcendent Wisdom - Mas‛ūd Āzarbāyijānī (حکمت اسرا, 2011)
What does “the meaning of life” mean? Does life have the same nature of material substances like stone and water, is it of the category of accidents and properties, or of type of events and processes? What is meant by “meaning” in “the meaning of life”? By “the purpose of life,” is it meant “function” of life or “value” of life? The Transcendent Wisdom is a philosophical system founded by Mulla Sadra and developed by his followers. Principality of existence, substantial motion, unity of the intellect, intelligent, and intelligible, the best created order, and the like are among basic principles of Transcendent Wisdom. Based on these principles and other foundations, life, consciousness, and love have spread throughout the universe. By “The best created order” is meant that divine wisdom has devised a plan within the material causes that as much creatures as possible could attain perfection; i.e., the laws governing the universe and human being be the best possible order so that the utmost good and the least evil befall human being. In other words, it is the “divine providence” that calls for the best possible order. The meaning of life for human being in Transcendent Wisdom refers to the philosophy of life and God’s purpose of creation. Devising the levels of natural, vegetable, animal and human soul, Mullā Ñadrā sees the evolution of the soul in agreement with the process of the movement of substance in the matter beginning from matter and going beyond on account of which resurrection takes place for the human spirit. Starting from the material intellect, the substantial motion of the soul, would not come to an end by reaching the acquired intellect (al-aql al-mustafād); for the fourth stage of the spiritual life of the soul, i.e., the level of connection with the active intellect (al- aql al-fa āl) or the Holy Spirit, actualizes the spiritual ecstasy and derivation from the light and knowledge. This is the meaning of life.